2021
DOI: 10.1016/j.jtauto.2021.100120
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease in the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic has had an impact on global health. Design The impact of the COVID-19 pandemic on patients with coeliac disease was assessed in the present review. Results The incidence of coeliac disease and the problems associated with coeliac disease increased during the COVID-19 pandemic. Adherence to the diet is crucial for the patient's health and quality of life since the only approved therapy for coeliac disease is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
0
16
0
1
Order By: Relevance
“…This COVID-19 pandemic has revealed shortcomings in the education of patients with CD, but especially those associated with T1DM or IBD, for GFD compliance. Adherence of CD patients to GFD during the COVID-19 pandemic improved their QOL and prevented unwanted complications [ 185 ].…”
Section: Discussionmentioning
confidence: 99%
“…This COVID-19 pandemic has revealed shortcomings in the education of patients with CD, but especially those associated with T1DM or IBD, for GFD compliance. Adherence of CD patients to GFD during the COVID-19 pandemic improved their QOL and prevented unwanted complications [ 185 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study reports immunological data on the relationship between COVID-19 and CD, using 2 distinct research approaches and including cohorts of patients/controls not yet vaccinated against SARS-CoV-2. Most scientific publications that evaluate the impact of COVID-19 disease on CD have focused on data collected through interviews or population-based analysis and have reported clinical, biochemical, and histological findings (8)(9)(10)(17)(18)(19)(20). However, to the best of our knowledge, only a few, incomplete, and conflicting laboratory data have been published on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…celiac crisis To date, despite the potential relevance for CD clinical practice, the impact of SARS-CoV-2 on CD incidence is not clear (8)(9)(10). Although COVID-19's impact has been investigated in other autoimmune diseases (11), only web-or telephone-based survey data have been reported on the frequency of COVID-19 immunity in CD patients or on the development of CD autoimmunity following COVID-19 infection.…”
Section: What Is Newmentioning
confidence: 99%
“…Further, Zimmermann and Curtis suggested that HLA-DQ2 or HLA-DQ8, which confer a genetic predisposition to CD, may be the drivers of lower responses to vaccination in CD patients [27]. Moreover, Lerner [28] stated that, while CD does not increase the likelihood of COVID-19 infection, parts of the CD population might be at high risk [29]. Zhen et al Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lerner [ 28 ] stated that, while CD does not increase the likelihood of COVID-19 infection, parts of the CD population might be at high risk [ 29 ]. Zhen et al .…”
Section: Discussionmentioning
confidence: 99%